Oestrus induction treatment in different sheep breeds out of the breeding season - Oláh, János; Egerszegi, István; Jávor, András; Szabó, Mária; Csízi, István; Monori, István (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
Aim of the study was to compare effectiveness of oestrus induction treatment in five sheep breeds out of the breeding season. Alltogether 236 ewes were used in the trial: Dorper (n=46), White Dorper (n=23), Suffolk (n=90), Ile de France (n=58) és Berrichon du Cher (n=19). The treatment was performed out of the breeding season in April-May. For oestrus induction gestagen sponges were used (Chronogest®, Intervet, 30 mg FGA). After 14 days sponges were removed and 400-500IU eCG were injected immediately. 30-36 hours after eCG application natural mating was performed. Pregnancy was checked by ultrasound 45-60 days after mating. Pregnancy rate was 57.8% in Suffolk and it reached 75.5% after remating ewes in consequitive cycle. In Berrichon du Cher the same parameters were 67% and 100% respectively. Pregnancy rate was 74% in Dorper, 70% in White Dorper and 69% in Ile de France breeds. Prolificacy rate was 1.29 in Berrichon du Cher, 1.56 in Suffolk, 1.60 in Ile de France, 1,67 in Dorper and 1.22 in White Dorper ewes. It could be concluded that oestrus induction treatment could be used successfully in these breeds out of the breeding season with further benefits.